High thermal stability and low dielectric constant of soluble polyimides containing asymmetric bulky pendant groups. Issue 12 (2nd December 2021) - Zheng, Hui; Wang, Chenyi; Ma, Yan; Tao, Zhengwang; Zhao, Xiaoyan; Li, Jian; Ren, Qiang
Abstract: Two new aromatic diamines with asymmetric structure: 3, 5-bis(trifluoromethyl) phenyl-2, 4-diaminobenzene (2a ) and 3, 5-dimethylphenyl-2, 4-diaminobenzene (2b ), were synthesized by a facile two-step reaction. The resulting polyimides (PI 3a -3c and 4a -4c ) containing asymmetric bulky pendant groups were prepared by one-step solution polycondensation through these diamines with three different dianhydride monomers, respectively. The polymers displayed good solubility and film forming ability, and the flexible films could be obtained conveniently by casting their solution. It was worth noting that these films have low dielectric constant and high thermal stability. Their dielectric constants were in the range of 2.68–3.20 (measured at 1 MHz), and their glass transition temperatures ( T g ) were in the range of 278–331 °C. The 10% weight loss temperatures of these polyimides in N2 and air atmosphere were above 543 °C and 585 °C, respectively. Their UV cut-off wavelengths were lower than 358 nm, and their wavelength at 80% light transmittance was between 431–468 nm. Moreover, they also exhibited good mechanical properties with tensile strength, initial modulus, and elongation at break values of 72.6–81.3 MPa, 1.7–2.2 GPa, and 5%–10%, respectively. Graphical Abstract: UF0001